2014
DOI: 10.2319/112913-877.1
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of three-dimensional perioral soft tissue changes in dentoalveolar protrusion patients after orthodontic treatment using a structured light scanner

Abstract: Objective: To evaluate the three-dimensional (3D) perioral soft tissue changes after orthodontic treatment in patients with dentoalveolar protrusion using structured light-based scanners. Materials and Methods: Forty-four Korean adults (19 men and 25 women, 21.4 6 3.4 years) with dentoalveolar protrusion treated by extraction of all four first premolars and then en masse retraction with maximum anchorage were evaluated. Lateral cephalograms and 3D facial scans were obtained before treatment (T1) and immediatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 20 publications
2
28
0
Order By: Relevance
“…To minimize the influence of sex on soft tissue changes following the incisor movement, only female patients were included in this study. Some studies have reported that the ratio between lip change and incisor retraction ranged from 1:0.45 to 1.25 for the upper lip, and from 1:1.2 to 1:6.2 for the lower lip in nongrowing patients with bimaxillary protrusion [19,20]. In addition to the changes of lip position, the incisor retraction could also induce soft tissue thickness changes [19,21].…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the influence of sex on soft tissue changes following the incisor movement, only female patients were included in this study. Some studies have reported that the ratio between lip change and incisor retraction ranged from 1:0.45 to 1.25 for the upper lip, and from 1:1.2 to 1:6.2 for the lower lip in nongrowing patients with bimaxillary protrusion [19,20]. In addition to the changes of lip position, the incisor retraction could also induce soft tissue thickness changes [19,21].…”
Section: Discussionmentioning
confidence: 99%
“…The origin (point 0, 0, 0) was set at soft tissue nasion. 9 The x-axis (left-right/transverse) was defined as the plane connecting right and left pupil points. 19 The y-axis (up-down/vertical) was defined as the plane formed by the perpendicular bisector of the segment connecting right and left pupil points.…”
Section: Image Analysismentioning
confidence: 99%
“…8 This is an important limitation, because incisor movement can also induce lip changes lateral to the midline. 9 Stereophotogrammetry is a 3D surface imaging technique that compares multiple photographs from various angles to construct a 3D model of the surface. 10 It is quick, non-invasive, 10 accurate, and reliable.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve these goals, it is necessary to create a balance between the soft and hard tissues, including the nose, lips, and jaw, and it is important to consider variability among individuals. 1 Among the facial soft tissue changes resulting from orthodontic treatment, there is particular interest in changes in the position and contour of the lips, and various methods of predicting posttreatment soft tissue changes have been reported to establish a diagnosis and treatment plan. [2][3][4][5] Choi et al 2 reported that in adult female patients with Class II Division 1 malocclusion, the ratios of movement between labrale superioris (Ls) and labrale inferioris (Li) to the extent of anterior teeth retraction are 1:0.45 and 1:2.08, respectively, and that the amount of posterior movement of Ls is correlated with posterior movement of the maxillary incisal edge.…”
Section: Introductionmentioning
confidence: 99%